Pengaruh Padat Tebar Terhadap Pertumbuhan Dan Kualitas Udang Windu (Penaeus monodon) Pada Sistem Nurseri - Aris Candra Prihantoro; Sri Waluyo; Yudha Trinoegraha Adiputra; Rara Diantari; Wardiyanto Wardiyanto (AQUASAINS, 2015)
The low productivity during extensive culture of tiger shrimp (Penaeus monodon) may caused by disability to environmental adaptation of shrimp during cultured period. Nursery system build up to minimize this constrains and enhances shrimp growth, quality and variation in natural pond system. Nursery system is cultured method to take care shrimp during post larvae to juvenile size within 14 days. The objective of this research is to measure the growth and the quality of post larvae shrimp during nursery system at different density which is 750; 1250; 1750 and 2250 shrimps/m2, respectively. The observation of juvenile quality was done to observe the digestive tract, weight variation, necrosis and parasite fouling. In the other side, growth observation was observed by the total length and the body weight. The result showedgrowth and quality of shrimp significantly differentwithin different density. In contrast survival rate of shrimp in differeny density not significantly different. The density of 750 shrimp/m2during nursery system in extensive  shrimp culture showed optimum in growth and quality.Shrimp production rose optimum size at 2250 shrimp/m2. The simulation of economic analysis  of shrimp production showed benefit to farmer in 1750 shrimp/m2 of density. This study support shrimp production in traditional method may increase with nursery system  and additional feed in short period (2 weeks).